Exercise training increases spatial memory via reducing contralateral hippocampal NMDAR subunits expression in intracerebral hemorrhage rats - Zheng S (Dove Medical Press, 2019)
Shulin Zheng,1 Feixue Zhang,1 Qiusheng Liu,2 Rui Jian,1 Min Yang11Department of Rehabilitation Medicine, Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan 646000, People’s Republic of China; 2Department of Cardiovascular Medicine, Luzhou Traditional Chinese Medicine Hospital, Luzhou, Sichuan 646000, People’s Republic of ChinaObjective: The aim of this study was to explore the effect of exercise training on spatial memory in rats with intracerebral hemorrhage (ICH) and to analyze its related neurobiological mechanisms.Methods: A total of 26 Sprague-Dawley rats were randomly divided into 3 groups: exercise (EX) group undergoing exercise training after ICH, model (MD) group and sham-operated (SM) group. The ICH rats model were induced by infusion of type I collagenase into caudate nucleus of rats. Morris water maze (MWM) test was performed at the same time in three groups to evaluate spatial memory in rats. All rats were sacrificed for evaluation of expression of N-methyl-d-aspartate receptor 1 (NR1) and N-methyl-d-aspartate receptor 2B (NR2B) in the CA3 region of the hippocampus by Western blot.Results: MWM test results showed that the spatial memory of MD group was significantly decreased compared to that of SM operation group (P<0.05), while exercise training significantly improved the spatial memory of rats with cerebral hemorrhage (P<0.05). Western blot analysis showed that exercise training significantly decreased the expression of NR1 and NR2B in CA3 region of the contralateral hippocampus (P<0.05), but there was no significant difference between MD and SM groups (P>0.05).Conclusion: Exercise training improves the spatial memory in the rats with ICH via down-regulating NR1 and NR2B expression in CA3 region of the contralateral hippocampus.Keywords: exercise training, intracerebral hemorrhage, NR1, NR2B, hippocampus